Neutrophil to lymphocyte ratio and risk of neoplastic progression in patients with Barrett’s esophagus - Peleg, Noam; Schmilovitz-Weiss, Hemda; Shamah, Steven; Schwartz, Ariel; Dotan, Iris; Sapoznikov, Boris (Endoscopy, 2020)
Background Patient’s with Barrett’s esophagus (BE) are at risk of progression to esophageal adenocarcinoma (EAC). Neutrophil to lymphocyte ratio (NLR) was found to be a predictor of poor prognosis in patients with EAC; however, its performance in premalignant esophageal lesions is vague. We aimed to evaluate the utility of NLR as a predictor of histologic progression in patients with BE. Methods A prospective cohort of patients with proven BE in a tertiary referral center was retrospectively analyzed. All biopsies were reviewed by an expert gastrointestinal pathologist. The discriminatory capacity of NLR was evaluated by area under the receiver operating characteristic (AUC) curve analysis and Cox regression analysis. Results 324 patients (mean age 62.3 years, 241 [74.4 %] males) were included in the final analysis. Overall, 13 patients demonstrated histologic progression to neoplasia over a mean follow-up of 3.7 years (progression risk 1.0 % per year). The AUC of NLR for progression to high grade dysplasia (HGD) or EAC was 0.88 (95 % confidence interval [CI] 0.83 – 0.96), and baseline NLR was associated with a 3-fold increase of progression to HGD and EAC during follow-up (hazard ratio [HR] 3.2, 95 %CI 1.5 – 5.8; P < 0.001). Notably, in a subgroup analysis of patients with nondysplastic BE (NDBE) at presentation, NLR was also a risk factor for histologic progression (HR 2.4, 95 %CI 1.7 – 3.4; P < 0.001). Conclusion NLR predicted histologic progression in patients with BE. Patients with NDBE and NLR above 2.4 can be considered for specific surveillance programs with shorter intervals between sessions.